Photopolymerized maleilated chitosan/thiol-terminated poly (vinyl alcohol) hydrogels as potential tissue engineering scaffolds. (15th March 2018) - Zhou, Yingshan; Zhao, Shuyan; Zhang, Can; Liang, Kaili; Li, Jun; Yang, Hongjun; Gu, Shaojin; Bai, Zikui; Ye, Dezhan; Xu, Weilin
Highlights: Photocrosslinkable maleilated chitosan with high acrylate substitution was synthesized. The MCS/TPVA thiol-ene hydrogels could gel rapidly and have improved mechanical property close to native tissue. The hydrogels had good biocompatibility. Abstract: Photocrosslinkable hydrogels composed of natural materials exhibit great application potential in tissue engineering scaffolds. However, weak formation and poor mechanical property can usually be a limitation. Herein, the photo-clickable thiol-ene hydrogels based chitosan were synthesized using photopolymerization of maleic chitosan (MCS) and thiol-terminated poly (vinyl alcohol) (TPVA) in the presence of a biocompatible photoinitiator. Rheological property and absorbing behavior of the MCS/TPVA hydrogels could be tailored by varying the amount of TPVA in the feed. There was strong intermolecular hydrogen bonding between the molecules of MCS and TPVA. Notably, the MCS/TPVA hydrogel (MT-3) exhibited rapid gelation behavior (<120 s), improved stiff (G' = ∼5500 Pa) and compressive strength (0.285 ± 0.014 MPa), which were important for hydrogel scaffolds, especially for injectable hydrogel scaffolds. Photocrosslinked MCS/TPVA hydrogels was cytocompatible and could promote the L929 cells attachment and proliferation, showing their potential as tissue engineering scaffolds.